Rethinking the geography of distress in nineteenth-century Ireland: Excess mortality and the Land War - Eoin McLaughlin; Niall Whelehan (Queen's University Centre for Economic History (QUCEH), 2024)
Analysis of excess mortality holds the potential to revise understandings of key moments in modern Irish history. Yet aside from studies of the Great Famine, it has been neglected by historians of Ireland. Examining rates of excess mortality across post-Famine Ireland reveals that the Land War crisis of 1877-1882, a transformational period, was one of the worst public health crises of modern Irish history. In fact, during the years 1878-1880 excess mortality levels were much higher than during any other period from when registration records began in 1864 up to the present day. Western regions, particularly Co. Mayo, have long been considered the worst affected by this crisis, but from the perspective of excess mortality, we establish that this was an islandwide crisis and one that was more severe that previously understood. The study of excess mortality in Irish history has been neglected partly because of some concerns expressed by scholars about the reliability of the source material in the annual statistical reports of the Registrar General. Yet, we document the reliability of the registers by cross-referencing with census returns, demonstrating their accuracy in the 1870s and 1880s, and their importance as sources to provide vital insights and context in modern Irish history.
Keywords: N13; N33; I18; 330; Land War; Excess Mortality; Ireland